Economic Regionalization in Western Europe: Asia-Pacific Economies (Macroeconomic Core: Microeconomic Optimization) - Dutta, Manoranjan (American Economic Review, 1992)
In the 1990's and beyond, the search for an optimum framework for studies in international economics is in order. The dynamics of two sets of economic events, one in Europe, (the emergence of a single economic region, the European Community [EC] and the other in Asia (Japan's economic achievement plus the industrialization and economic growth of certain Asia-Pacific economies) suggests that a new multipolar world economy is emerging. In this global context the EC paradigm of economic regionalization, providing a macroeconomic core for microeconomic optimization, warrants attention.